STUDY OF THE ESSENTIAL OIL OF THE “YARETA” Smallanthus parviceps (Blake) Rob - Neves Ordóñez, Gianella (2020)
In the present investigation, a phytochemical study was carried out on the essential oil of the “yareta” (Smallanthus parviceps (Blake) Rob), collected in Ayacucho in the Chumpi district. The essential oil was obtained by the distillation method by dragging with steam, from 1.50 kg of fresh plant, its smell can be defined as citric, pleasant and balsamic, in addition the essential oil has an anti-inflammatory power according to the ethnobotanical information of the plant. Regarding its characterization, the physicochemical properties were first determined, which indicates that "yareta" oil contains 0.06% of essential oil whose density is 0,75g/mL and a pH: 6, then its components were determined by CG-MS gas chromatography. Its major components are: α-felandrene, p-cymene, caryophyllene, the α-curcumene isomers and β-curcumene, to α-pymene and to caryophyllene oxide.